Food security and technological solutions in military settings: a bibliometric and thematic analysis - Razali, Mohamad Azli; Md Radzi, Elias; Tazijan, Farina Nozakiah; Rahmatullah Khan, Hussin Khan; Din, Norrina; Rezo, Khairul Hidayat; Zainol, Noorliza (Universiti Teknologi MARA, Perlis, 2025)
The integration of advanced technologies, such as the Internet of Things (IoT) and artificial intelligence (AI), is increasingly recognized as pivotal in transforming food security strategies within military settings. This study employs a bibliometric and thematic analysis to examine the role of these technological innovations in enhancing the resilience of military food supply chains. Using the Scopus and Web of Science databases, we explored key research trends from 2019 to 2024, focusing on how emerging technologies address critical vulnerabilities in food systems exposed by global crises, such as the COVID-19 pandemic and geopolitical conflicts. Findings reveal that the United States and China are leading the charge in research output, with significant contributions from other nations. Technological advancements, including IoT and AI, are driving innovations in real-time monitoring, predictive analytics, and optimization of military food systems, ensuring supply chain integrity even in high-risk environments. The study's contribution lies in its comprehensive mapping of the evolving landscape of military food security, providing insights into the intersection of technology and operations. These findings offer valuable guidance for future research and policymaking, encouraging further investment in resilient, tech-driven food security solutions for military contexts.